PENGARUH POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR IPS (Universitas Negeri Semarang, 2017)
This research aimed to describe the parenting system, the social science learning (IPS) outcomes, and the influence of parenting system towards the learning outcomes in social science learning (IPS). The research design was a quantitative research with a correlational method. The population was 344 fourth grade students of elementary schools in Gugus Kresna West Semarang District and the sample was 103 students. The sampling technique was proportional random sampling. The data were derived from test, questionnaire, and documentation. To analyze the prerequisite test using normality test and linearity test. Meanwhile, the hypothesis test using simple regression. The result showed that 88.3% parents of the four grade students of elementary schools tend to apply the democratic parenting system, meanwhile, the application of parenting system in general was quite good with the percentage about 61.16%, the learning outcomes of social science was very good (35,9 %). The analyze showed positive correlation (r value 0.351) and the significance value 0.000. The contribution of the parenting system towards the social science learning outcomes was 12.3%. Conclution from this research was there was a positive and significant influence between the parenting system and social science learning outcomes.